Decreasing Mitochondrial Fission Prevents Cholestatic Liver Injury - Yu, Tianzheng (J Biol Chem, 2014)
Mitochondria frequently change their shape through fission and fusion in response to physiological stimuli as well as pathological insults. Disrupted mitochondrial morphology has been observed in cholestatic liver disease. However, the role of mitochondrial shape change in cholestasis is not defined. In this study, using in vitro and in vivo models of bile acid-induced liver injury, we investigated the contribution of mitochondrial morphology to the pathogenesis of cholestatic liver disease. We found that the toxic bile salt glycochenodeoxycholate (GCDC) rapidly fragmented mitochondria, both in primary mouse hepatocytes and in the bile transporter-expressing hepatic cell line McNtcp.24, leading to a significant increase in cell death. GCDC-induced mitochondrial fragmentation was associated with an increase in reactive oxygen species (ROS) levels. We found that preventing mitochondrial fragmentation in GCDC by inhibiting mitochondrial fission significantly decreased not only ROS levels but also cell death. We also induced cholestasis in mouse livers via common bile duct ligation. Using a transgenic mouse model inducibly expressing a dominant-negative fission mutant specifically in the liver, we demonstrated that decreasing mitochondrial fission substantially diminished ROS levels, liver injury, and fibrosis under cholestatic conditions. Taken together, our results provide new evidence that controlling mitochondrial fission is an effective strategy for ameliorating cholestatic liver injury.